Yapayao-Isneg Tribe- Ethnozoological Beliefs, Traditions and Practices in the Current Century - Gonzales, Arlene Cerna Urgena; Briones, Catherine B (Asian Journal of Multidisciplinary Studies, 2019)
The belief and practices indigenous people demonstrate on the use of animals place the reverence they communicate to these God-given creatures. Animals for these people marks omens, serve as guides, commune them with their deities, sanctify their rituals, and heal them of their illnesses. The Yapayao-Isneg Tribe from Adams, Ilocos Norte is but one of the many indigenous people living in that part of the Philippines who, just like any other tribes, possesses unique knowledge about animals that symbolizes their culture. Their communion with animals as well as their perception on the significance of these animals in their daily lives speaks volumes that would differentiate them from the rest of the other tribes. From the information gathered during the course of the study, it was stipulated by the interviewees that their belief and customs, their tradition and culture with regards to the importance of animals varies as to the occasion which necessitates the participation of the animals – from hunting to farming, during sickness and healing, in omens and even in death rites.